Urgensi Layanan Bimbingan dan Konseling: Survey Analisis Kebutuhan Layanan untuk Mahasiswa Institut Agama Islam Negeri Kediri (Jurusan Bimbingan dan Konseling Islam, 2020)
This research is based on a student problem study at IAIN Kediri, where the Guidance and Counseling (BK) service is still not implemented. This study aims to describe the urgency of BK services and what BK service needs for students at Islamic Religious Colleges in Kediri City. The method used in this research is a quantitative approach to survey design with a cross-sectional survey design type. The research instrument used was a questionnaire to analyze student needs and the data analysis used was descriptive statistics to describe the urgency of BK services for students at PTKI. The results of data analysis show that the need for BK services is indicated by the percentage of problems experienced by students at PTKI, namely problems in the learning sector 28.59%, problems in the career sector 27.65%, then problems in the social sector 22.08%, and in the personal field. amounted to 21.68%. Thus, the urgency of BK services can be taken into consideration in making policies at IAIN Kediri.